Sundanese classical dance as a representation of aesthetic values and noble culture in West Java - Ria Sabaria; Cece Sobarna; Teddi Muhtadin; Juju Masunah (Cogent Arts & Humanities)
Sundanese Classical Dance is a dance developed in a noble environment in West Java whose people speak Sundanese and have a historical background and cultural values that are mutually agreed upon. This study aims to discuss the aesthetic values, ethics and manners, and cultural values in Sundanese Classical Dance, specifically Keurseus Dance danced by male dancers and Sulintang Dance danced by female dancers. This research uses a qualitative approach with ethnographic methods to reveal these values represented by dance movements, make-up and dance costumes. The data were collected through observation, interviews, documentation studies, and literature reviews. The results showed that the aesthetic, ethical and values manners in Sundanese Classical Dance show social behavior, social system, and nobility identity. Social behavior is expressed by subtlety, politeness, neatness, and order reflected in the beauty of dance movements, while the social system is patriarchal. Sundanese nobility identity is reflected in makeup and dance attire. The values manners are reflected in the overall expression of the dance and daylife such as discipline, patience, and responsibility. The results of this study have implications for the relay of aesthetic and cultural values of the next generation as heirs of Sundanese Classical Dance.